Postoperative Pain Comparison Between Open Hemorrhoidectomy and Stapled Hemorrhoidopexy on Internal Hemorrhoid at Siloam Hospitals Lippo Village - Taufik Sudirman; Alvin Wiguna (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Background: Hemorrhoids have a prevalence of 4,4%. Surgery is one of the modalities for treating hemorrrhoids. The method accepted as the